International trade and income distribution: The effect of corporate governance regimes - Hartmut Egger; Peter H. Egger; Douglas Nelson (Review of International Economics, 2024)
Abstract This paper introduces a model of corporate governance into the general oligopolistic equilibrium theory of international trade. Corporate governance defines the influence of workers and capital owners on manager contract and, through this contract, the scope of these two groups for subsequent rent extraction in the wage/employment negotiation between firms and unions. If capital owners have dictatorship over the manager contract, they can extract the full bargaining surplus and eliminate the union wage premium. If workers have dictatorship over the manager contract they can achieve a wage premium, driving the income of capital owners down to zero. In this setting, opening up to trade is to the detriment of the income group whose interests are decisive for the manager contract. This shows that distributional conflicts materializing from trade can be considerably different for countries with differing corporate governance regimes. Foreign investment allows capital owners in unionized industries to flee from disadvantageous corporate governance regimes at home, eliminating union wage premia and lowering manager remuneration in countries with corporate governance regimes that give workers dictatorship over manager contracts.
Keywords: 330; corporate governance; foreign investment; international trade; labor unions; rent extraction